1992
DOI: 10.1111/j.1438-8677.1992.tb00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Nectar Secretion Pattern and Removal Effects in Six Argentinean Pitcairnioideae (Bromeliaceae)

Abstract: Nectar secretion pattern and effects of nectar removal were analyzed in six hummingbird‐pollinated Argentinean Pitcairnioideae: Abromeitiella brevifolia. A. lorentziana, Deuterocohnia longipetala. Dyckia floribunda, D. ragonesei and Puya spathacea. Flower lifetime was determined in each case. Nectar volume, concentration and sugar production were measured from bud opening till fading of flowers at different time intervals according to the species' flower life‐span. Nectar volume varies while nectar concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 35 publications
2
46
1
6
Order By: Relevance
“…Essa medida permitiu calcular a produção média de néctar e, consequentemente, determinar o padrão de secreção de néctar. Em outro grupo de flores foram feitas medidas repetidas em cada flor com intervalos de duas horas, mantendo as flores ensacadas entre as medições, de acordo com Galetto & Bernardello (1992). Esse conjunto de flores foi dividido em cinco grupos com seis flores cada; as medições do néctar do primeiro grupo iniciaram às 7h00, do segundo grupo às 9h00 e assim sucessivamente até o último grupo, às 15h00.…”
Section: Methodsunclassified
“…Essa medida permitiu calcular a produção média de néctar e, consequentemente, determinar o padrão de secreção de néctar. Em outro grupo de flores foram feitas medidas repetidas em cada flor com intervalos de duas horas, mantendo as flores ensacadas entre as medições, de acordo com Galetto & Bernardello (1992). Esse conjunto de flores foi dividido em cinco grupos com seis flores cada; as medições do néctar do primeiro grupo iniciaram às 7h00, do segundo grupo às 9h00 e assim sucessivamente até o último grupo, às 15h00.…”
Section: Methodsunclassified
“…Unfortunately, most studies that evaluate the effects of nectar thieves and robbers on nectar availability have measured differences in volume of nectar (McDade & Kinsman 1980, Morris 1996, Roubik 1982, Roubik et al 1985, and the same approach is provided by studies investigating the role of flower mites as nectar thieves (Colwell 1995, Cruz et al 2007, Lara & Ornelas 2001, 2002b. The problem in measuring only nectar volume and sugar concentration is that these variables vary greatly with period of the day (as in the present study), with nectar removal and flower age (Galetto & Bernadello 1992), but also with abiotic factors such as temperature and atmospheric relative humidity (Galetto & Bernadello 2005). Thus, for a better assessment of nectar production costs and energetic content, it is necessary to transform samples with volume and concentration in sugar biomass (Galetto & Bernadello 2005).…”
Section: Discussionmentioning
confidence: 86%
“…Bromeliad nectar is mainly composed of water and sugars, with the proportions of fructose, glucose and sucrose varying among species within three subfamilies, producing insignificant quantities of amino acids and no lipids or proteins (Bernadello et al 1991). Galetto & Bernadello (1992) observed that nectar removal increased secretion but decreased sugar concentration in some bromeliad species. However, these effects did not alter the total amount of sugar secreted, except for Puya spathacea, in which nectar removal decreased both nectar volume and sugar amount.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reabsorção do néctar permite que a planta economize recursos importantes que não foram utilizados pelos polinizadores (Burquez & Corbet 1991;Luyt & Johnson 2002). Outra possibilidade é que as flores desta espécie sejam estimuladas a produzir mais néctar conforme este recurso seja retirado pelos visitantes florais (Gill 1988;Galetto & Bernardello 1992). Neste caso, a produção de néctar pode ter sido subestimada, já que este foi retirado a cada duas horas e as flores foram visitadas em todos os horários de observação, ou seja, pelo menos uma vez por hora.…”
Section: Resultsunclassified